The Influence of Work Motivation and Work Discipline on Teacher Performance at SDN Kebalen 02 Bekasi - Nurhasan; Aswin Naldi Sahim; Widya Nengsih (STMIK Indonesia Banda Aceh, 2026)
This study aims to identify and analyze the influence of work motivation and work discipline on teacher performance at SDN Kebalen 02 Bekasi, both partially and simultaneously. The study employs a quantitative method with descriptive and verificative approaches. Data were collected using questionnaire instruments. Respondents were 32 teachers at SDN Kebalen 02 Bekasi. Multiple linear regression analysis with SPSS version 25 was used. The findings show that work motivation has a positive effect on teacher performance at SDN Kebalen 02 Bekasi. Work discipline also positively influences teacher performance. The study further reveals that work motivation and work discipline simultaneously affect teacher performance at SDN Kebalen 02 Bekasi. The simultaneous effect amounts to 74.1% (R2 = 0.741), while the remaining 25.9% is influenced by other factors not examined in this study. It can be concluded that combining improved work motivation and work discipline significantly enhances teacher performance at SDN Kebalen 02 Bekasi.